Tools for Podcasting - Olmsted, Jill (Open textbook library., 2019)
Welcome! If you’re interested in learning about the growing universe of podcasting, how it works and finding tools and inspiration to create your own podcast, this online resource is for you. My focus is on audio podcasting and this practical guide will help you navigate the technology and best practices in an easy-to-understand handbook. You will also find many audio and video clips that provide examples and video tutorials leading you through editing software, vocal delivery, promotion ideas and more. All videos have closed captioning and there is an extensive section on the importance of transcription of podcasts to enable web accessibility for the deaf, hearing impaired and language learning audiences. There is also an emphasis on diversity and inclusion with resources listing mentorships and employment opportunities. For even more information click on the extensive links throughout this e-book. In addition, each chapter has learning objectives and there are practice exercises in Appendix C at the end of the e-book along with additional resources about podcasting from newsletters and conferences to how-to-create tools and podcast recommendations. Podcasting is a dynamic way to use your smarts and creativity to tell stories about compelling subjects. This handbook provides instruction and tools to produce your own podcast — whether you are a professional in journalism, the arts, sciences, business or law, an activist or just someone who has a story to tell. The tools discussed are focused on keeping costs low for entry-level podcasters and designed to help anyone who wants to record, edit and distribute podcasts.